I believe the answer is C
Answer:to revise or edit
anything that can be made in the non draft one
Explanation:
Answer:
T₂ = 123.9 N, θ = 66.2º
Explanation:
To solve this exercise we use the law of equilibrium, since the diaphragm does not appear, let's use the adjoint to see the forces in the system.
The tension T1 = 100 N, we create a reference frame centered on the pole
X axis
T₁ₓ -
= 0
T_{2x}= T₁ₓ
Y axis y
T_{1y} + T_{2y} - 200N = 0
T_{2y} = 200 -T_{1y}
let's use trigonometry to find the component of the stresses
sin 60 = T_{1y} / T₁
cos 60 = t₁ₓ / T₁
T_{1y} = T₁ sin 60
T1x = T₁ cos 60
T_{1y}y = 100 sin 60 = 86.6 N
T₁ₓ = 100 cos 60 = 50 N
for voltage 2 it is done in the same way
T_{2y} = T₂ sin θ
T₂ₓ = T₂ cos θ
we substitute
T₂ sin θ= 200 - 86.6 = 113.4
T₂ cos θ = 50 (1)
to solve the system we divide the two equations
tan θ = 113.4 / 50
θ = tan⁻¹ 2,268
θ = 66.2º
we caption in equation 1
T₂ cos 66.2 = 50
T₂ = 50 / cos 66.2
T₂ = 123.9 N
Let the data is as following
mass of payload = "m"
mass of Moon = "M"
now we know that we place the payload from the position on the surface of moon to the position of 5r from the surface
So in this case we can say that change in the gravitational potential energy is equal to the work done to move the mass from one position to other
so it is given by
![W = U_f - U_i](https://tex.z-dn.net/?f=W%20%3D%20U_f%20-%20U_i)
we know that
![U_f = -\frac{GMm}{6r}](https://tex.z-dn.net/?f=U_f%20%3D%20-%5Cfrac%7BGMm%7D%7B6r%7D)
![U_i = -\frac{GMm}{r}](https://tex.z-dn.net/?f=U_i%20%3D%20-%5Cfrac%7BGMm%7D%7Br%7D)
now from above formula
![W = -\frac{GMm}{6r} + \frac{GMm}{r}](https://tex.z-dn.net/?f=W%20%3D%20-%5Cfrac%7BGMm%7D%7B6r%7D%20%2B%20%5Cfrac%7BGMm%7D%7Br%7D%20)
![W = \frac{5GMm}{6r}](https://tex.z-dn.net/?f=W%20%3D%20%5Cfrac%7B5GMm%7D%7B6r%7D)
so above is the work done to move the mass from surface to given altitude